2012
DOI: 10.1590/s0102-86502012000200015
|View full text |Cite
|
Sign up to set email alerts
|

Chemoprevention with green propolis green propolis extracted in L-lysine versus carcinogenesis promotion with L-lysine in N-Butyl-N-[4-hydroxybutyl] nitrosamine (BBN) induced rat bladder cancer

Abstract: -ORIGINAL ARTICLEEXPERIMENTAL ABSTRACT PURPOSE:To determine the effects of green propolis extracted in L-lysine (WSDP) and of L-lysine for 40 weeks on induced rat bladder carcinogenesis. METHODS:The animals (groups I, II, III, IV, V and VI) received BBN during 14 weeks. Group I was treated with propolis 30 days prior received BBN, and then these animals were treated daily with propolis; Groups II and III was treated with subcutaneous and oral propolis (respectively) concurrently with BBN. The animals of Group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 18 publications
0
23
0
Order By: Relevance
“…In paper accept for publication, based on the same experimental model shows that L-lysine was able to stimulate carcinoma multiplicity and invasion in BBN-induced rat bladder cancer 28 .…”
Section: Discussionmentioning
confidence: 97%
“…In paper accept for publication, based on the same experimental model shows that L-lysine was able to stimulate carcinoma multiplicity and invasion in BBN-induced rat bladder cancer 28 .…”
Section: Discussionmentioning
confidence: 97%
“…This work is a continuation of earlier studies published by Dornelas et al 7,9 whose objective was to evaluate the effect of green propolis and L-lysine on carcinogenesis and angiogenesis in rats subjected to chemical carcinogenesis of the bladder. In the earlier studies, we found that propolis administered to rats inhibited angiogenesis and bladder carcinogenesis in this model at the doses studied and that L-lysine promoted bladder carcinogenesis.…”
Section: Discussionmentioning
confidence: 76%
“…MNT is utilized to detect chromosomal damage of the mitotic spindle, in which during the maturation of erythroblasts, the nucleus is expelled from the cell and in the absence of damage through breaks or damage in the mitotic spindle, where no residual chromatid (micronucleus) remains inside the cell. Propolis is a resin produced by bees that has various antineoplasic 2 , antiinflammatory 3 , immunomodulatory 4 , antibacterial 5 and antiangiogenesis properties 6,7 . L-lysine is an essential amino acid and has been utilized in the extraction of propolis since the patented proposal of Nicolov et al 8 up to recent publications 2,3,7,9 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study on rats submitted to chemical carcinogenesis of the bladder, L-lysine was found to promote, but not initiate, bladder cancer 6 .…”
Section: ■ Introductionmentioning
confidence: 94%